2019
DOI: 10.3892/ol.2019.10469
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic factors for patients with primary pulmonary non‑Hodgkin's lymphoma: A 16‑year single‑center retrospective study

Abstract: Primary pulmonary non-Hodgkin's lymphoma (PP-NHL) is a rare entity with non-specific symptoms and radiographic findings, as well as a difficult preoperative diagnosis. A limited number of studies have described PP-NHL in Chinese patients. The goal of the present study was to improve early diagnosis by examining prognostic factors in patients with PP-NHL. Therefore, a total of 29 patients with PP-NHL were included in the study between January 2001 and June 2017, including 14 with aggressive-type and 15 with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…From literature, aggressive PPL tended to have earlier stages (IE‐IIE) in 96%, 100%, 98%, and 100% of cases, respectively 3,11,16,17 . The LDH level was confirmed to be normal in 79% and 55.2% of patients, 17,18 and no bone marrow involvement was present 3,16,17 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…From literature, aggressive PPL tended to have earlier stages (IE‐IIE) in 96%, 100%, 98%, and 100% of cases, respectively 3,11,16,17 . The LDH level was confirmed to be normal in 79% and 55.2% of patients, 17,18 and no bone marrow involvement was present 3,16,17 .…”
Section: Discussionmentioning
confidence: 87%
“…No specific prognostic factors influencing survival have been clearly defined in several papers for PPL patients 3,6,16‐18 …”
Section: Discussionmentioning
confidence: 99%
“…The radiographic appearance of PPL showed a variety of findings, such as single or multiple nodules, masses, ill-defined infiltrates and consolidations [8]. This suggests that any radiological abnormality of the lung parenchyma contains the possibility of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, 18 F-2-deoxy-2-fluoro-D-glucose-positron emission tomography/CT has developed rapidly in the field of staging of lymphoma and efficacy evaluation of treatment due to its more sensitive display than conventional CT. Lee et al [ 31 ] showed higher standardized uptake values (SUVs) in systemic ALCL than in other types of aggressive T-cell lymphoma, as well as higher SUVs in ALK-positive ALCL patients than in ALK-negative ones. It is necessary for definite diagnosis by CT-guided percutaneous needle lung biopsies as soon as possible[ 32 ].…”
Section: Discussionmentioning
confidence: 99%